A night to remember [videorecording (DVD)] - Baker, Roy; More, Kenneth, 1914-1982; Blackman, Honor, 1925-2020-; Goodliffe, Michael, 1914-1976; Lord, Walter, 1917-2002 (Criterion collection, 1998)
Tells the story of the sinking of the Titanic.